2022
DOI: 10.3390/biology11020184
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Swab Real Time-PCR in Leishmania infantum Seropositive Dogs: Diagnostic and Prognostic Values

Abstract: Conjunctival swabs (CS) are the most promising non-invasive samples for the diagnosis and the regular screening of Leishmania infantum infection in dogs although knowledge on their diagnostic performance is still inconclusive. This study evaluates CS real time-PCR (qPCR) analysis for the diagnosis of canine leishmaniosis (CanL) and its prognostic value in seropositive dogs from an endemic area. In October 2020 (T0), 26 dogs were enrolled, divided in two groups according to anti-L. infantum antibody titres (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…infantum positive blood samples corresponded to animals that had antibody titers higher than 1:640, with lower Ct values in qPCR, which agrees with the higher sensitivity of minicircle qPCR [ 39 ]. Indeed, the usefulness of blood qPCR to detect Leishmania is correlated with antibody titration [ 47 ], and as high positive predictive value based on clinical evaluation [ 48 ]. Nonetheless, given the limited group of dogs selected, discarding a co-infection or a previous exposure to L .…”
Section: Discussionmentioning
confidence: 99%
“…infantum positive blood samples corresponded to animals that had antibody titers higher than 1:640, with lower Ct values in qPCR, which agrees with the higher sensitivity of minicircle qPCR [ 39 ]. Indeed, the usefulness of blood qPCR to detect Leishmania is correlated with antibody titration [ 47 ], and as high positive predictive value based on clinical evaluation [ 48 ]. Nonetheless, given the limited group of dogs selected, discarding a co-infection or a previous exposure to L .…”
Section: Discussionmentioning
confidence: 99%
“…Each dog underwent a complete physical examination, and a clinical sign-based score for CanL ranging from 0 to 19 was assigned ( 18 ). Blood samples were collected from either the cephalic or jugular veins and placed in K3 EDTA tube (2 ml) to undergo complete blood count (CBC) and ESR evaluation, as well as in sodium citrate (2.5 ml) to obtain plasma and perform fibrinogen concentration measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription-qPCR (qRT-PCR) on conjunctival swabs has proven to be a very sensitive non-invasive technique to screen dogs for leishmaniosis, as it has the potential to detect infection earlier than if it were performed on other tissues, even before any symptoms become evident [ 21 23 ]. However, it has been suggested that a positive result only by qRT-PCR on conjunctival swabs, in the absence of a positive result with any other diagnostic test or the presence of any clinical sign, should be considered with caution [ 24 ]. With the exclusion of this subsect, L. infantum efficacy for Leros increased from 87.8% to 93.9%, which is in total agreement with the findings from Crete.…”
Section: Discussionmentioning
confidence: 99%